The Influence of Brand Image and Brand Awareness on Consumer Purchasing Decisions of Fore Cimahi Coffee on the GoFood Platform - MUHIBAN, Ayi; PUTRI, Adel Leani (Journal of Entrepreneurial and Business Diversity, 2025)
Purpose:This research was conducted on Kopi Fore Cimahi consumers on the GoFood platform in RT05 RW04, Padasuka Village. This study aimed to determine the influence of brand image and brand awareness on purchasing decisions, both partially and simultaneously.Methodology:The research method used in this study is descriptive and associative. In this study, the unit of analysis is all consumers who have purchased or consumed Kopi Fore Cimahi in the RT05 RW04 area of Padasuka Village. The sample in this study is 100 respondents, where sampling is taken with certain considerations or criteria.Findings:Based on the research results it shows that there is a good influence, both partially and simultaneously, on the brand image and brand awareness variables on the purchasing decision variables.Implication:The influence of brand image on purchasing decisions is 15.8%. The influence of brand awareness on purchasing decisions is 46.7%. The influence of brand image and brand awareness on purchasing decisions is 62.6%.